Serum CHI3L1 as a biomarker of interstitial lung disease in rheumatoid arthritis - Yu, Rui; Liu, Xiaomin; Deng, Xiaoyue; Li, Siting; Wang, Yifei; Zhang, Yan; Ke, Dan; Yan, Rui; Wang, Qian; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng; et al. (Frontiers in Immunology, 2023)
Background: Interstitial lung disease (ILD) is a relatively prevalent extra-articular manifestation of rheumatoid arthritis (RA) and contributes to significant morbidity and mortality. This study aimed to analyze the association between chitinase-3 like-protein-1(CHI3L1) and the presence of RA-ILD.Methods: A total of 239 RA patients fulfilling the American Rheumatism Association (ACR) 1987 revised criteria were enrolled and subclassified as RA-ILD and RA-nILD based on the results of high-resolution computed tomography scans (HRCT) of the chest. The disease activity of RA was assessed by Disease Activity Score for 28 joints (DAS28) and categorized as high, moderate, low, and remission. Chemiluminescence immunoassays were applied to determine the serum levels of CHI3L1. Univariate analysis was performed and the receiver operating characteristics (ROC) curves were plotted to evaluate the correlation between RA-ILD and CHI3L1.Results: Among the eligible RA patients studied, 60 (25.1%) patients were diagnosed with RA-ILD. Compared with RA-nILD, RA patients with ILD had significantly higher median age (median [IQR], 68.